Kinerja Pelayanan Pemerintah Kecamatan (Studi Kasus Pada Kantor Camat Tambelan Kabupaten Kepulauan Riau) = Performance of Sub-District Government Service: A Case Study at Tambelan Sub-District Office of Kepulauan Riau Re - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The research aims to find out the public service performance that is conducted at Tambelan Sub-District and to identify the influencing factors on the public service performance. Meanwhile the research uses descriptive method with descriptive qualitative technique of data analysis where data obtained are qualitative and quantitative data. The qualitative data are presented descriptively, whereas the quantitative data are given in the form of a table derived from interview and spreading questionnaires. This study found out that the service performance of Tambelan Sub-District could be said good on the aspect of responsiveness, efficiency of cost, and oriented service. While the other aspects are accountability, efficiency of time, and facility for the service could not be said good. The good perfor-mance is very dominantly determined by professionalism factor, incentive system, collaboration when compared with mission-vision factor that is merely slogan and structural factor is not yet completely filled by the officials. However, for the future, it needs to establish a certain standard of service time, improvement or supply of service facilities, implementing a given mission and vision as well as addition of officials to fill the empty position. Consequently, the performance of Tambelan Sub-District will be better.